What gangs aren’t: contrasting gangs with other collectives - Bouchard, Martin (The Oxford handbook of gangs and society, 2024)
This chapter aims to compare gangs with delinquent peer groups, organized crime groups, and other collectives to tease out what, precisely, makes a gang a gang. It proposes several dimensions to consider when aiming to determine whether a collective looks more like a gang or another form - some focus on how collectives approach crime and others focus on the organizational aspects of collectives. In the end, these dimensions combine in unique ways that capture the wide variations observed in gangs worldwide. The chapter discusses the measurement of each dimension, hoping to stimulate future research in this area, but also to help scholars and practitioners recognize what gangs are and what they aren’t.